Dairy Enterprise – 2,400 Lactating Cows (Freestall) - Dhuyvetter, Kevin C.; Smith, John F.; Harner III, Joseph P.; Brouk, Micheal (My University, 2011)
This publication describes the production costs and returns for a dairy enterprise with 2400 lactating cows in a freestall system.
MF2442_2011_12
Keywords: MF2442; Economics; Livestock; MF